Morbimortality study of infection in patients undergoing different types of dialysis in a renal replacement therapy center - Curty,Natália Fabiane Ridão (2014)
INTRODUCTION: Renal replacement therapy is the treatment of end-stage chronic kidney disease and can be performed through dialysis catheters, arteriovenous fistulas/grafts, and peritoneal dialysis. Patients are usually immunocompromised and exposed to invasive procedures, leading to high rates of infection and increased mortality.OBJECTIVES: To compare the prevalence of infection and related deaths, as well as the sensitivity profile of the putative bacteria in patients treated with peritoneal dialysis, arteriovenous fistula hemodialysis and catheter hemodialysis.METHODS: This is case-control study. Six hundred forty-four patients undergoing renal replacement therapy were selected. Patients were divided into three groups according to the modality of dialysis treatment: peritoneal dialysis (126 patients), arteriovenous fistula hemodialysis (326 patients), and catheter hemodialysis (192 patients).RESULTS: One hundred sixteen patients (18.01%) developed infection. There was a higher incidence of infection in the peritoneal dialysis group (44 patients; 34.92%; OR: 3.32; CI 95% = 2.13-5.17; p = 0.0001). In the catheter hemodialysis group, 48 patients (25%) had infection (OR: 1.88; CI 95%: 1.24-2.85; p = 0.0035). In the arteriovenous fistula hemodialysis group, 24 patients (7.36%) developed infection (OR: 0.19; CI 95%: 0.12-0.31; p = 0.0001). Five patients (4.31%) died due to infection (four in the peritoneal dialysis group and one in the catheter hemodialysis group). There were no deaths due to infection in the arteriovenous fistula hemodialysis group.CONCLUSIONS: Peritoneal dialysis is the treatment with greater risk of infection and mortality, followed by catheter hemodialysis. The lowest risk of infection and mortality was observed in arteriovenous fistula hemodialysis group.